Potential production of RDF from municipal solid waste mechanical treatment and selective collection rejected streams - Duarte, Diana (2017)
In order to fulfill legal requirements, adequate alternatives to traditional municipal waste landfilling must be found. The valorization of some residual streams from municipal solid waste (MSW) treatment plants are among them. The purpose of this study is to characterize the rejected streams resulting from the mechanical treatment of municipal solid waste and from the yellow waste container selective collection, in order to evaluate the potential of their valorization as Refuse Derived Fuel (RDF). To accomplish this purpose, two sampling campaigns were done. Physical characteristics, proximate analysis, heating value and chlorine content were determined. As expected, results show that the refused stream from mechanical treatment and from the selective collection are rather different in overall composition, water content, energetic matter and ashes, as well as heating value and chlorine, with the last showing higher calorific value and lower moisture, therefore superior energy recovery availability. Preliminary data allows us to conclude that studied materials have a very interesting potential to be used as RDF.